Suffolk County Courthouse, Pemberton Square, ca. 1895-1905 - Unknown (Tufts Archival Research Center, 2005)
Elevated view looking northwest of the Suffolk County Courthouse in Pemberton Square. In the lower right corner are horse-drawn vehicles including a delivery cart for Houghton and Dutton, dry goods. George A. Clough, architect 7 x 9 Photographs